Femoral Nerve Injury as a Complication of Percutaneous Simple Renal Cyst Sclerotherapy with Ethanol: A Case Report - Ashraf, Alireza (Hindawi Publishing Corporation, 2012)
Simple renal cysts are benign, common, and often asymptomatic disease in old age, sometimes treated with ethanol sclerotherapy. We report a case of iatrogenic femoral nerve injury following percutaneous injection of ethanol into a renal cyst under sedation. The percutaneous injection was guided by sonography. At the end of the procedure, the cyst ruptured so the patient progressed to loss of consciousness due to alcohol intoxication. Ethanol was damaged to the femoral nerve, so patient was developed with limping, numbness, and weakness in anteromedial aspect of the right thigh. To the best of our knowledge, this is the first report of femoral nerve injury caused by percutaneous simple renal cyst sclerotherapy with ethanol. This rare event has not been previously described, Physicians should be aware of the possibility of this complication.